Do Children’s “Best Interests” Matter When Tracing Their Filiation in Quebec Civil Law ? - Campbell, Angela (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2023)
This essay offers a commentary on the intersection between the best interests principle and the law of filiation in Quebec. It highlights the tension between best interests and the positive law of filiation, highlighting the implications for those most vulnerable in family law disputes who have been central to Professor Goubau’s scholarship. The analysis here is premised on a review of four relatively recent decisions handed down by Quebec courts, each distinct in its context. The first considers circumstances of assisted procreation or “parental projects” that result in more than two prospective parents ; the second addresses intercultural adoption contexts ; the third examines determinations of filiation where a child’s birth ensues from a surrogacy agreement ; and the fourth explores how the law deals with stepparent-stepchild relationships. In each context, a judgment is featured to explore how the law intersects with the best interests principle. While none of the judgments are intended to be representative of the state of the law in a given area, each offers an example to illustrate how courts negotiate tensions between the positive law and the best interests principle. While judges will have varying degrees of discretion in different contexts to consider this principle, they acknowledge the tension and seek to reconcile it in a manner that at once foregrounds children’s interests while also correctly applying and interpreting relevant legal authorities.